The front façade of the Baiturrahman Grand Mosque in Banda Aceh from past until present - Septiyana, Dina; Irwansyah, Mirza; Dewi, Cut (Universiti Teknologi MARA, Perak, 2025)
As the Dutch colonists conquered the Sultanate of Aceh, they burned the palace and rebuilt Aceh by erasing traces of royal glory. Consequently, many of this region's existing historical buildings have Dutch colonial architecture characteristics. Aceh was nicknamed "Seuramoe Mekkah", which means the veranda of Mecca, and is still known to date. Banda Aceh is one of Indonesia’s historical cities and part of the Indonesian Heritage Cities Network (JKPI). As a historic old city and the capital of Aceh Province, Banda Aceh holds many appealing memories and information, one of which is the existence of the Baiturrahman Grand Mosque as a vital historical and cultural site. The mosque has undergone numerous historical processes, several renovations, and significant physical developments. Before the renovations, the Baiturrahman Grand Mosque had a colonialstyle image. After the latest renovation, with the addition of 12 electric hydraulic umbrellas, the mosque’s facade was changed to resemble the Nabawi Mosque. The present study aims to analyze the transformation and evaluate the image of the Baiturrahman Grand Mosque building following the latest renovation. A descriptive-qualitative method was employed, with interviews, documentation, and direct observation as data collection techniques. The results indicate that the transformation of the Baiturrahman Grand Mosque from the use of the first dome to the addition of the umbrellas and the renovation represent highly significant changes. Moreover, the image of the grand mosque building remains maintained, with only the surrounding area being changed.